Examen especial a la gestión de política conozca a su empleado en la Cooperativa de Ahorro y Crédito San José Ltda., agencia Guaranda, provincia Bolívar, de enero 2020 a diciembre de 2021 - Patín Patín, Alex Fernando (2023)
Increasingly, Financial Institutions are subject to the commission of irregular acts resulting from the actions of white-collar criminals who use cunning rather than force, such as employees, among one of the IFIs affected by this type of punishable act among one of them is internal fraud, there are the COACs. These actions cause repercussions such as deterioration of the patrimony and institutional image of the companies in which illegal acts are committed. In this sense, the objective of this research is to carry out a special examination of the know-your-employee policy management at the San José Ltda. Savings and Credit Cooperative, Guaranda agency, Bolívar province, from January 2020 to December 2021. The type of research was descriptive and bibliographical and documentary, with a qualitative and quantitative approach, the research methods were deductive, inductive, analytical-synthetic and historical-logical. For data collection, survey and interview techniques were used through a questionnaire and a guide. The main result was that in the Savings and Credit Cooperative, "San José" Ltd., Guaranda agency, only special examinations of traditional audits have been applied, more than the type that, according to their nature of work, allows identifying fraudulent acts. Keywords: irregular acts, credit union, special exam, know your employee policy.